2006
DOI: 10.1016/j.jim.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A modified α-galactosyl ceramide for staining and stimulating natural killer T cells

Abstract: CD1d presentation of alpha-galactosyl ceramides to natural killer T cells has been a focal point of the study of regulatory T cells. KRN7000, an alpha-galactosyl ceramide originally generated from structure activity studies of antitumor properties of marine sponge glycolipids, is currently the most commonly used agonist ligand and is used to stain NKT cells. However, this glycolipid suffers from poor solubility and availability. We have developed an alpha-galactosyl ceramide with improved solubility over KRN70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
145
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 13 publications
1
145
0
Order By: Relevance
“…In the current study, we identified CD1d-restricted NKT cells by CD1d tetramers loaded with ␣-GalCer analog PBS57 (18). At 3 h following reperfusion, we observed an increase in the percentage of NKT cells producing IFN-␥.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In the current study, we identified CD1d-restricted NKT cells by CD1d tetramers loaded with ␣-GalCer analog PBS57 (18). At 3 h following reperfusion, we observed an increase in the percentage of NKT cells producing IFN-␥.…”
Section: Discussionmentioning
confidence: 53%
“…To identify CD1d-restricted NKT cells, we labeled kidney cells with anti-mouse CD45-FITC, anti-mouse TCR␤-PE, and CD1d tetramer-Alexa 647 loaded with PBS57 (1:500), an analog of ␣-galactosyl ceramide (␣GalCer) that yields results identical with ␣GalCer (National Institutes of Health tetramer facility; www. yerkes.emory.edu/TETRAMER/CD1d_Tetramers.html) (18). Unloaded CD1d tetramer-Alexa 647 was used as control.…”
Section: Identification Of Nkt Cells and Quantitation Of Intracellulamentioning
confidence: 99%
“…Spleen cell suspensions were incubated in round-bottom plates in RPMI1640 medium supplemented with glutamine, antibiotics, and 10% FCS (Sigma Aldrich, St. Louis, MO, USA) with 50 ng/mL plate-bound anti-CD3 antibody (eBioscience, San Diego, CA, USA), PMA/Ionomycin (Cell Stimulation Cocktail, eBioscience, San Diego, CA, USA), 0.1-100 ng/mL α-GalCer [85] or an equivalent amount of DMSO (Carl Roth, Karlsruhe, Germany). CD11b-and Nur77-GFP-expression on as well as IFN-γ-and T-betexpression in iNKT cells were analyzed using FACS.…”
Section: In Vitro Stimulation Of Inkt Cellsmentioning
confidence: 99%
“…It can also be applied to humans, opening a new avenue for iNKT cell-based immunotherapy that has the potential to provide patients with therapeutic levels of iNKT cells throughout life. TCRs (16). We included TCR Vβ8 staining to focus on the dominant Vβ8 + population of mouse iNKT cells (1,2).…”
Section: Cloning Of Inkt Tcr Genes and Construction Of Retroviral Delmentioning
confidence: 99%